MicroRNA-143 inhibits cell growth by targeting ERK5 and MAP3K7 in breast cancer - Zhou,L.L. (2017)
This study aimed to investigate the function and mechanism of microRNA-143 (miR-143) in the occurrence and development of breast cancer (BC). A total of 30 BC tissues, 30 corresponding noncancerous tissues, and 10 normal control (NC) breast tissues were obtained to detect the levels of miR-143, extracellular signal-regulated kinase 5 (ERK5) and mitogen-activated protein 3 kinase 7 (MAP3K7) using RT-qPCR, western blotting or immunohistochemistry. The correlation of miR-143 with ERK5 or MAP3K7 was evaluated using Pearson correlation analysis. MCF-7 cells were transiently transfected with miR-143 mimic, miR-143 inhibitor, miR-143 mimic/inhibitor + si-ERK5, si-MAP3K7 or si-cyclin D1. Then, cell growth was evaluated by MTT assay and the expressions of phospho-ERK5 (p-ERK5), ERK5, p-MAP3K7, MAP3K7 and cyclin D1 were detected by western blotting. Results showed that, compared with noncancerous tissues or NC breast tissues, miR-143 level was decreased, while p-ERK5, ERK5, p-MAP3K7 and MAP3K7 expressions were increased in BC tissues (all P<0.01). The miR-143 level was negatively correlated with the mRNA level of ERK5 or MAP3K7 (r=-4.231 or r=-4.280, P<0.01). In addition, up-regulated miR-143 significantly decreased the expressions of p-ERK5, ERK5, p-MAP3K7, MAP3K7 and cyclin D1 (all P<0.01), as well as cell viability in MCF-7 cells (all P<0.05) while the effect of down-regulated miR-143 was the opposite. In conclusion, both ERK5 and MAP3K7 may be the target genes of miR-143. Increased expression of miR-143 can inhibit cell growth, which may be associated with ERK5 and MAP3K7 expressions in BC.